Communication and Genealogical System of Mosque Imam: a Study in East Lombok and North Lombok, Indonesia - Hakim, M Sabron Sukmanul; Manggola, Alen; Ridlo, Ali; Rifa’i, Akhmad; Masri, Mohammed Sharin Haji (Analisa: Journal of Social Science and Religion, 2023)
Genealogy as a system is generally used to preserve a tradition, culture, thought, science, or power. However, in the Raudhatul Muttaqin Mosque, Kotaraja East Lombok and Al-Bayani Mosque, Gondang, North Lombok, this system is actually used to determine the imam, which in Islam and the government there are no rules regarding the obligatory prayer imam from certain descendants. The purpose of the research is to identify how the descendants of Sheikh H. L. Abdurrahman and Amiq Sahabuddin communicate with the community in implementing the genealogical system of mosque imam in Kotaraja and Gondang. The research method used is a qualitative type of a case study and data were collected through observation, documentation, and interviews with the generations of Shaykh H. L. Abdurrahman and Amiq Sahabuddin as mosque imam, community leaders, and villagers. The study concluded that the main actors of persuasion to the community are the descendants of the imam who are supported by the power of the message, media, argumentation, psychological appeal, credibility, and legitimacy of the community. The persuasion process of the descendants of the imam displays convincing expressions and contains various values, both religious, customary, social, and educational values, so that the community can accept it well.